Adsorption of Cu(II) and Zn(II) onto Activated Carbon from Oil Palm Empty Fruit Bunch Prepared by Two-Step Acid Treatment and Microwave-Assisted Pyrolysis - Thotsaporn Somsiripan; Chayanoot Sangwichien; Kanogwan Tohdee; Surat Semmad (Adsorption Science & Technology)
This study explores the feasibility of biochar-based activated carbon derived from oil palm empty fruit bunch (EFB) as a potential precursor for the preparation of activated carbon via 2-step H3PO4 activation under microwave-assisted pyrolysis (2ACEFB). The characterization of EFB and 2ACEFB was observed by FTIR and BET, and chemical composition was determined using proximate and elemental analysis data. The adsorptive removal of Cu(II) and Zn(II) from an aqueous solution was studied, and the effects of metal concentration and solution pH were also investigated. The pseudo-second-order equation was properly described, providing the best fit to the observed experimental data. The adsorption capacities of Cu(II) and Zn(II) onto the EFB were 20.28 and 18.06 mg/g, respectively, and improved by 2.04- and 1.89-fold onto the 2ACEFB. The potential of 2ACEFB was also proved by adsorbent reusability with five consecutive circles of the batch experiment without regeneration or treatment. This study demonstrated that 2ACEFB is an efficient adsorbent for eliminating heavy metals from aqueous solutions.